RATING EVALUATION OF SELF-REGULATING ORGANIZATIONS OF ARBITRATION MANAGERS AS A MECHANISM TO IMPROVE THEIR PERFORMANCE - S. I. Lutsenko (Стратегические решения и риск-менеджмент)
The influence of macroeconomic factors and company characteristics on the financial decisions (financing sources, a choice of model of optimum financing) are considered. The economic policy of state allows to understand made decisions the company concerning the capital structure. The given work allows to draw certain conclusions on why the Russian companies, in a greater degree, adhere to the pecking order theory. On analogies to the public companies, the state in the field of a debt policy also adheres to the pecking order theory.